Basal Study on Power Control Strategy for Fuel Cell/Battery Hybrid Vehicle - Dingyue Chen; Xia Li; Lihao Chen; Yonghui Zhang; Li Yang; Songsong Li (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
In order to enhance the fuel economy of hybrid vehicle and increase the mileage of continuation of journey, the power control strategy (PCS) is as significant as component sizing in achieving optimal fuel economy of the fuel cell/battery hybrid vehicle (FCBHV). The models of FCBHV structure and optimal power control strategy are developed by electric vehicle simulation software ADVISOR which uses a hybrid backward/forward approach. The results demonstrate that the proposed control strategy can satisfy the power requirement for two standard driving cycles and achieve the power distribution among various power sources. The comprehensive comparisons with the power tracking controller (PTC) which is wide adopted in ADVISOR verify that the proposed control strategy has better rationality and validity in terms of fuel economy and dynamic property in two standard driving cycles. Therefore, the proposed strategy will provide a novel approach for the advanced power control system of FCBHV.